2022
DOI: 10.1097/qad.0000000000003324
|View full text |Cite
|
Sign up to set email alerts
|

Gut-dependent inflammation and alterations of the intestinal microbiota in individuals with perinatal HIV exposure and different HIV serostatus

Abstract: Objective:HIV-exposed infected (HEI) and uninfected (HEU) children represent the two possible outcomes of maternal HIV infection. Modifications of the intestinal microbiome have been linked to clinical vulnerability in both settings, yet whether HEI and HEU differ in terms of gut impairment and peripheral inflammation/activation is unknown.Design:We performed a cross-sectional, pilot study on fecal and plasma microbiome as well as plasma markers of gut damage, microbial translocation, inflammation and immune a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
11
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(16 citation statements)
references
References 49 publications
3
11
2
Order By: Relevance
“…Assessing the relationship between HIV-associated microbial dysbiosis and systemic inflammation, we identified significant correlations between the relative abundance of certain taxa and plasma inflammatory biomarkers, warranting further investigations. Our findings were inconsistent with studies in Australian cART-naïve adults and Italian cART-experienced children where correlation of gut microbiota with systemic cytokines and microbial translocation markers was not found ( 17 , 50 ).…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Assessing the relationship between HIV-associated microbial dysbiosis and systemic inflammation, we identified significant correlations between the relative abundance of certain taxa and plasma inflammatory biomarkers, warranting further investigations. Our findings were inconsistent with studies in Australian cART-naïve adults and Italian cART-experienced children where correlation of gut microbiota with systemic cytokines and microbial translocation markers was not found ( 17 , 50 ).…”
Section: Discussioncontrasting
confidence: 99%
“…HIV infection can lead to a decrease in gut microbiota diversity, potentially resulting in the loss of beneficial bacteria and the proliferation of harmful ones ( 64 ). In contrast, the gut microbiota richness and evenness in our study were similar between the HIV-infected and HIV-uninfected groups in line with previous studies in cART-treated American and Spanish adults as well as South African and Italian children ( 37 , 50 , 65 68 ). In contrast, in other studies, reduced ( 16 , 17 , 64 , 69 ) or increased ( 41 ) alpha diversity was observed in HIV-infected cART-naïve individuals.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…As increasingly recognized for other solid tumors, the tumor microenvironment might be relevant for the development of malignancy [56][57][58][59], and coinfection with other viruses appears to contribute to an altered epithelial microenvironment. The changes in microbiome profile along with local inflammation and bacterial translocation related to HIV infection [60] could also promote the oncogenic transformation of HPV-infected cells, and impact the immune response to HPV infection.…”
Section: Biological Mechanismsmentioning
confidence: 99%
“…In their article, Gut-dependent inflammation and alterations of the intestinal microbiota in individuals with perinatal HIV exposure and different HIV serostatus, Tincati et al [5] compared the blood and faecal microbiome as well as markers of gut damage, microbial translocation, and immune activation/inflammation in infected (HEI) and exposed (HEU) children over the age of 1 year. Despite having similar microbiota profiles in plasma and faeces, differences were observed in faecal beta-diversity and relative abundance.…”
mentioning
confidence: 99%